2019
DOI: 10.1186/s12872-019-1095-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of circulating BMP9 with coronary heart disease and hypertension in Chinese populations

Abstract: Background Bone morphogenetic protein9 (BMP9) has been reported to have a role in vascular development. However, there is still a lack of information regarding the association between circulating BMP9 levels and cardiovascular disease in humans. The goal of this study is to measure circulating BMP9 concentrations in patients with essential hypertension (HTN), coronary heart disease (CHD) and HTN + CHD, and evaluates the relationship between circulating BMP9 and these cardiovascular diseases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…One cross-sectional study showed that circulating BMP-9 levels were negatively correlated with hypertension and CAD (Liu et al, 2019). In a recent study, and BMP-10 double knockout mice, and they found dramatic changes, such as a thinner vascular smooth muscle layer, decreased blood pressure and dilated aortic, pulmonary, cardiac arteries and mesenteric arteries (Wang et al, 2021).…”
Section: The Bmp Family and Hypertensionmentioning
confidence: 98%
“…One cross-sectional study showed that circulating BMP-9 levels were negatively correlated with hypertension and CAD (Liu et al, 2019). In a recent study, and BMP-10 double knockout mice, and they found dramatic changes, such as a thinner vascular smooth muscle layer, decreased blood pressure and dilated aortic, pulmonary, cardiac arteries and mesenteric arteries (Wang et al, 2021).…”
Section: The Bmp Family and Hypertensionmentioning
confidence: 98%
“…BMP9 circulating levels have also been shown to be significantly lower in patients with vascular malformations, hypertension, and coronary heart disease 98,140,141 . Elevated circulating BMP10 has also been shown to predict atrial fibrillation ablation 142 …”
Section: Bmp9 and Bmp10 As Biomarkersmentioning
confidence: 99%
“…BMP9 circulating levels have also been shown to be significantly lower in patients with vascular malformations, hypertension, and coronary heart disease. 98,140,141 Elevated circulating BMP10 has also been shown to predict atrial fibrillation ablation. 142 Circulating BMP9 has also been measured in a small cohort (n = 10) of patients with systemic inflammatory response syndrome (SIRS) and sepsis, and was found to be significantly reduced compared to healthy controls.…”
Section: Modification Of Bmp9 and Bmp10 Circulating Levels In Pathologiesmentioning
confidence: 99%
“…GDF-2 is produced by the liver and maintains vascular quiescence, promotes osteogenesis, and is associated with improved glucose metabolism and insulin sensitivity [ 56 , 57 ]. GDF-2 has been suggested as a biomarker for cardiovascular disease since its levels are lower in individuals with essential hypertension and coronary heart disease compared with controls [ 58 ]. In a mouse model, fetal GDF-2 levels increase until birth and remain high 3 weeks postnatal, indicating a role for GDF-2 in development [ 59 ].…”
Section: Discussionmentioning
confidence: 99%